2007
DOI: 10.1097/jto.0b013e31805fea3a
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cancer in New Zealand: Patterns of Secondary Care and Implications for Survival

Abstract: This cohort was characterized by high comorbidity and advanced disease. Although similar to the United Kingdom, initial treatment rates were low in comparison with Australia and the United States, despite similar stage distributions. Overall, 50% of patients, including 30% with early-stage disease, did not receive initial anticancer treatment. Low anticancer treatment rates may contribute to poorer survival outcomes in New Zealand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
56
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 36 publications
6
56
1
Order By: Relevance
“…In our study 28.57% patients (29.46% of NSCLC and 23.44% of SCLC) didn't receive any anticancer treatment. These figures varies from 19% in USA, 33% in Australia, 37% in Scotland, and 50% in Ireland and New Zealand (Fry et al, 1999;Vinod et al, 2008;Erridge et al, 2008;Mahmud et al, 2003;Stevens et al, 2007). Vinod et al (2010) have addressed this issue in their study and found that in actual practice 20% patients didn't receive any treatment; however guideline recommendations for no treatment were there in only 4% patients.…”
Section: Discussionmentioning
confidence: 99%
“…In our study 28.57% patients (29.46% of NSCLC and 23.44% of SCLC) didn't receive any anticancer treatment. These figures varies from 19% in USA, 33% in Australia, 37% in Scotland, and 50% in Ireland and New Zealand (Fry et al, 1999;Vinod et al, 2008;Erridge et al, 2008;Mahmud et al, 2003;Stevens et al, 2007). Vinod et al (2010) have addressed this issue in their study and found that in actual practice 20% patients didn't receive any treatment; however guideline recommendations for no treatment were there in only 4% patients.…”
Section: Discussionmentioning
confidence: 99%
“…The discrepancy between studies might in part reflect a different population composition-that is, the Alberta population has a significantly smaller proportion of people of Asian ethnicity, a higher proportion of smokers, and a lower frequency of EGFR mutation compared with the other two provinces [37][38][39] . Internationally, the published rates of chemotherapy administration have all shown a favourable trend over time, although they vary widely, from less than 10% to more than 50% in developed countries 14,16,17,40 . Our outcomes would therefore be considered an outlier in comparison with those from other large retrospective studies.…”
Section: Figurementioning
confidence: 99%
“…Yet despite the demonstrated efficacy of systemic therapy, referral to mo after a diagnosis of advanced nsclc and administration of chemotherapy or targeted therapy remains suboptimal. The referral rates to mo are estimated to be 50%-70% for all nsclc patients and 30%-60% for all advanced nsclc patients [13][14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17][18][19][20] have addressed this issue in their study and found that in actual practice 20% patients didn't receive any treatment; however, guideline recommendations for no treatment were there in only 4% patients.…”
Section: Discussionmentioning
confidence: 99%